(untitled) - Kurtzig, Sandra L. (Boston, Mass., 1994)
This edition features a new introduction in which Kurtzig draws on her own experiences to provide insight into the sources of entrepreneurial success - leadership, vision, strategic thinking and the ability to make decisions and take risks.
Keywords: Computer industry,Công nghiệp máy tính; History,Lịch sử; United States,Hoa Kỳ